Long-term Evaluation of Constructed Wetland Efficiency for Domestic Wastewater Treatment under Temperate Climatic Conditions in Beijing, China - Liu, Zeyuan; Hien, Le; Tuan, Le Duc Anh; Xuyen, Nguyen Thi (Tropical Environment, Biology, and Technology, 2026)
This study evaluated the long-term performance of a constructed wetland (CW) system for domestic wastewater treatment under temperate climatic conditions in Beijing, China. The system, with a capacity of 400 m³/day serving approximately 3,500 people, was monitored over four years. The results showed stable treatment performance, with average effluent concentrations of COD 30.04 ± 8.49 mg/l, BOD₅ 10.53 ± 3.12 mg/l, TSS 8.87 ± 3.38 mg/l, TN 12.34 ± 2.88 mg/l, TP 0.54 ± 0.16 mg/l, and NH₄⁺ 4.85 ± 1.15 mg/l, all meeting the Chinese discharge standard GB 18918-2002 (Level IB). Removal efficiencies were higher for organic matter and TSS (up to 76.49% and 84.52% in summer) than for nutrients (TN 66.62%, TP 55.61%, NH₄⁺ 49.68%). Seasonal variation significantly affected performance, with winter efficiencies decreasing to 57.87% (COD) and 41.50% (NH₄⁺). Correlation analysis indicated that temperature was the dominant factor (r = 0.637–0.638, p < 0.01), while influent characteristics had moderate effects (r = 0.405–0.479). These results demonstrate that CW systems provide a stable and effective solution for decentralized wastewater treatment, although optimization is required to improve performance under low-temperature conditions.